Biosecurity as the main component of national security and its value base - Vardanyan, Bagrat (YSU Journal of International Affairs, 2023)
The modern world is going through a period of transformation. The formation of new power centers and the intensification of the struggle between them, as well as the increase in the importance of military power in that struggle, lead to a change in the structure of the world order and the formation of new rules and principles. Political conceptual documents are of special importance in the structure of the national security policy and decision-making process of each country, among the most important of which the national security concept or a document equivalent to it in its functions, which may have a different name based on the characteristics of the country, can be ranked among the most important. The concept of national security is a political document that contains the system of official views on the place and role of the state in the modern world, the national values, interests and goals of the state, the forces, means and capabilities of preventing and countering external and internal threats, as well as organizing the operation of the national security system. foundations and principles.The rapid globalization of science and technology, as well as the expansion of travel, trade and migration, together with positive effects, have brought to light threats and challenges of a qualitatively new nature, which require states to operate at the local, regional and global levels with new rules of the game, where the control and prevention of biological threats are crucial. Biosecurity issues are directly related to critical infrastructure and are threats at the national level.
Keywords: national security; biological security; biotechnology; biological threat; genetically modified organisms; biological weapons